2017
DOI: 10.1002/ps.4571
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sublethal effects of pesticides in the management of Polyphagotarsonemus latus (Banks) (Acari: Tarsonemidae) on Capsicum annuum L.

Abstract: The lethal and sublethal effects of abamectin, spiromesifen, azadirachtin and neem oil significantly affect P. latus population growth, as well as causing repellence to this mite on C. annuum, and they should be considered in the integrated pest management of this mite. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, their microscopic nature (<0.2 mm size) and hidden refuge coupled with specific biological characteristics such as short life cycle, female‐biased sex ratio, arrhenotokous reproduction and high fecundity (Rai et al, 2007) necessitate the repeated application of pesticides that could lead to the rapid development of resistance. Breda et al (2017) reported LC 90 values higher than their commercially recommended doses for abamectin and spiromesifen, indicating the selection of resistant populations of P. latus collected from Capsicum annuum at Brazil. Further, varying levels of resistance to diafenthiuron, dicofol, fenazaquin, propargite and spiromesifen were observed in the field‐collected populations of P. latus from India (Augustine et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, their microscopic nature (<0.2 mm size) and hidden refuge coupled with specific biological characteristics such as short life cycle, female‐biased sex ratio, arrhenotokous reproduction and high fecundity (Rai et al, 2007) necessitate the repeated application of pesticides that could lead to the rapid development of resistance. Breda et al (2017) reported LC 90 values higher than their commercially recommended doses for abamectin and spiromesifen, indicating the selection of resistant populations of P. latus collected from Capsicum annuum at Brazil. Further, varying levels of resistance to diafenthiuron, dicofol, fenazaquin, propargite and spiromesifen were observed in the field‐collected populations of P. latus from India (Augustine et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Its population increases rapidly under appropriate environmental conditions, especially when occurs in protected areas such as greenhouses. It also develops resistance to pesticides quickly (Reddy and Kumar 2016;Breda et al 2017). Although chemical control is still the most commonly used controlling approach to P. latus (De Saraiva et al 2016;Barbar 2017), it is necessary to nd environment friendly alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Its population increases rapidly under appropriate environmental conditions, especially when occurs in protected areas such as greenhouses. It also develops resistance to pesticides quickly (Reddy and Kumar 2016;Breda et al 2017). Although chemical control is still the most commonly used controlling approach to P. latus (De Saraiva et al 2016;Barbar 2017), it is necessary to nd environment friendly alternatives.…”
Section: Introductionmentioning
confidence: 99%